(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article reviews the theoretical and practical aspects of developing special paints based on nanoparticles that reflect infrared (IR) rays and reduce heat absorption. The possibility of controlling the optical and thermal properties of surfaces using nanoparticles is analyzed. The results of the study show that they are of great importance in increasing energy efficiency and reducing heat load in building materials and vehicles.